EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TERHADAP PRESTASI AKADEMIK SISWA KELAS X SMA NEGERI 1 TOMA - Ndruru, Wida Mawati (Universitas Nias Raya, 2025)
This research is motivated by the low academic achievement of students. The purpose of this study was to describe the level of academic achievement of students before and after the implementation of group guidance services and to test the effectiveness of group guidance services in improving academic achievement of class X students of SMA Negeri 1 Toma, especially in sociology subjects. The research method used was quantitative with the one-group pretest-posttest design. The research sample consisted of 26 students of class X-Anggrek who were selected using the total sampling technique. Data were collected through learning outcome tests before and after the provision of group guidance services, and analyzed using the Wilcoxon signed ranks test. Based on the results of this study, it shows that the results of the hypothesis test obtained a Zcount value of 3.88 with N = 26 and α = 0.05, because Zcount> 0.05. Thus, it can be concluded that the Ha Hypothesis is accepted which states that group guidance services are effective in improving academic achievement because of the treatments that have been given by researchers or guidance and counseling teachers to help students improve their academic achievement. Suggestions; 1) For schools, they should schedule guidance and counseling teachers in schools in accordance with Permendikbud No. 25 of 2024, 2) for guidance and counseling teachers, they should be able to motivate, guide, direct and provide understanding to students about the importance of improving academic achievement, 3) For subject teachers, teachers should be able to better understand how to improve students' academic achievement so that learning in the classroom is more effective, 4) For students, students are expected to be able to apply ways to improve academic achievement in every learning in the classroom, 5) For further researchers, it is hoped that they can conduct research on other aspects of learning to improve students' academic achievement.